The Effect of War to the Nigerian Educational Activities: A Systematic Review - Zainudin Abu Bakar; Darma Kabiru Rabiu (Journal of Education and Learning (EduLearn), 2018)
War is the leading cause of destruction to educational sector in Nigeria, in particular, the primary and secondary school education system. The focused of this review is to examine how the war affects the entire educational system of Nigeria by leading to the prevalence of numerous problems that hinder the successful achievement for “Educational for All” and the new Millennium Development Goal. The exploration activities of related references on the effect of war were systematically guided by PRISMA Statement which consists of a 27-item checklist and a four-phase flow diagram. The Prisma Diagram Generator was also utilized to generate the process of scrutinizing the articles. The end results render Nigeria as backward and the poverty-stricken nation that made it very difficult to support and sustain its educational sector according to global standard as enshrined by UNICEF.